Enhancing student motivation in reaction rate topics through the integration of Instagram-based learning media and the Student Teams-Achievement Divisions cooperative model - Widarti, Hayuni Retno; Amalia, Elvira Risva Firda; Rokhim, Deni Ainur (Eclética Química, 2025)
Instagram-based learning media can be applied in chemistry learning because it can be accessed at any time, it is not limited by distance or time if you have an internet network and adequate hardware and can increase student learning motivation. This study aimed to ascertain whether applying the Instagram-integrated Student Team-Achievement Divisions learning model and multi-representation strategies enhances student motivation on reaction rate topics. The Nonequivalent Control Group Design with the Quasi-Experimental technique is the research design. Using a random sampling technique, students from Malang Senior High School’s class XI-Science were selected as the research sample. Student learning motivation data was descriptively and quantitatively examined, and statistical tests, such as prerequisite analysis tests and hypothesis testing, were used to analyze data on learning outcomes. The results of this experimental research found that in the extremely high category, the percentage of students who were motivated to learn rose from 56 to 85%. These findings show the experimental class’s improvement in learning motivation outperformed that of the control class.